CPWF Volta V4 Main Message Poster - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2013)
Successful integrated water resources management depends on interactions between multiple actors at different scales, which is often beyond everyday considerations. The companion modeling-approach is a good framework to highlight interactions between actors and allows for a collective decision-making process to unfold.